Research on Emission Reduction Strategies of Building Materials Manufacturers and Real Estate Developers in the Context of Carbon Trading - Yao, Qingzhen; Shao, Liangshan (Frontiers in Environmental Science, 2022)
External carbon trading, free transfer between enterprises and, internal carbon trading are the primary forms of carbon trading between real estate enterprises and building materials enterprises. This paper establishes the Stackelberg game model under three conditions of carbon trading and analyzes the emission reduction strategies of real estate developers and building materials manufacturers. The results show that the low carbon degree of building materials is proportional to that of residential buildings and is affected by the external carbon trading price; The order quantity of building materials is directly proportional to the low carbon degree of building materials and housing and has nothing to do with the form of carbon trading; When only external carbon trading is carried out, the maximum profit of real estate developers is positively correlated with carbon quota and external carbon trading price, and the maximum profit of building materials manufacturers is positively correlated with carbon quota and negatively correlated with external carbon trading price. When internal carbon trading and external carbon trading coexist, the maximum profit of real estate developers increases with the rise of carbon quota, and the maximum profit of building materials manufacturers does not change significantly with the rise of carbon quota; Internal carbon trading can increase the profits of building materials manufacturers and reduce the selling prices of building materials, thereby increasing their enthusiasm for carbon emission reduction. An example is given to verify the effectiveness of the above conclusions.